2013
DOI: 10.1021/je400157s
|View full text |Cite
|
Sign up to set email alerts
|

High-Pressure Physicochemical Properties of Ethyl Caprylate and Ethyl Caprate

Abstract: The components of biodiesel derived from coconut oil or babassu oil such as ethyl caprylate and ethyl caprate are studied. The experimental speeds of sound in ethyl caprylate were reported at p = (0.1 to 101.32) MPa and at T = (292.90 to 318.32) K and in ethyl caprate at p = (0.1 to 101.32) MPa and at T = (292.90 to 318.28) K together with the experimental densities at 0.1 MPa for ethyl caprylate at T = (278.15 to 358.15) K and for ethyl caprate at T = (283.15 to 353.14) K as well as heat capacities were repor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
28
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(32 citation statements)
references
References 36 publications
3
28
1
Order By: Relevance
“…7. We can observed that the trends of the isobaric molar heat capacities of methyl caprate and methyl laurate with the variation of temperature are also almost the same, which is consistent with the conclusion obtained by Pauly et al [10] for the liquid isobaric molar heat capacities of fatty acid methyl esters at atmospheric pressure. Therefore, we can conclude that the number of carbon atoms in fatty acid group before the ester group has a significant effect on the isobaric molar heat capacities of fatty acid methyl esters, but it has a slight effect on …”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…7. We can observed that the trends of the isobaric molar heat capacities of methyl caprate and methyl laurate with the variation of temperature are also almost the same, which is consistent with the conclusion obtained by Pauly et al [10] for the liquid isobaric molar heat capacities of fatty acid methyl esters at atmospheric pressure. Therefore, we can conclude that the number of carbon atoms in fatty acid group before the ester group has a significant effect on the isobaric molar heat capacities of fatty acid methyl esters, but it has a slight effect on …”
Section: Resultssupporting
confidence: 92%
“…Fig. 3 shows the deviations between the experimental data in our work and those reported by Van Bommel et al [8] and Pauly et al [10] for the isobaric molar heat capacities of methyl caprate and methyl laurate at atmospheric pressure. It can be observed that our experimental results are consistent with those in literatures, showing a maximum absolute relative deviation of 1.2%.…”
Section: Resultscontrasting
confidence: 40%
See 1 more Smart Citation
“…Various types of long-chain fatty acids can be found in fatty feedstocks from which biodiesel can be obtained, resulting in different molecular structures of fatty acid esters in biodiesel. Different thermophysical characteristics result from various molecular structures, which impact the fuel performance, the exhaust gas content, and combustion efficacy in diesel engines [9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the addition of oxygenated fuels will affect thermophysical properties of diesel. So the study on thermophysical and transport properties of oxygenated fuels is required for a better understanding and improvement in engines [9], which include heat capacity [10], critical properties [11] and speed of sound [12], etc. Viscosity has a significant impact on the spray characteristics and combustion of the fuel [13].…”
Section: Introductionmentioning
confidence: 99%